Eksplorasi Mindful Parenting Pada Orangtua Anak Berkebutuhan Khusus: Studi Kualitatif - Alucyana, Alucyana; Yunita, Yenni; Raihana, Raihana; Evelyn, Rivaloni; Sari T, Ayu Novita (UIN Sultan Maulana Hasanudin Banten, 2026)
This study aims to explore the experiences of parents of children with special needs in implementing mindful parenting in their daily lives. The study used a qualitative approach with a phenomenological approach, involving six parents as purposively selected subjects. Data were collected through in-depth interviews, observation, and documentation, then analyzed using Miles and Huberman's interactive analysis technique. The results showed that most parents did not yet understand the concept of mindful parenting theoretically, but had applied some aspects intuitively. The main challenges faced included difficulty in emotional control, lack of empathetic communication, and the process of accepting the child's condition. Nevertheless, parents showed progress in self-acceptance and more adaptive parenting efforts over time.